DEMOKRASI DAN MULTI KULTURALISME DALAM KONTESTASI DAKWAH ISLAM - Ahmad, Rusdin (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi; Vol 13 No 1 (2017), 2017)
The essence of democracy is justice and equality in all aspects of life, including rights as the individual, citizen, and the God’s creatures. The plurality of God’s creatures is a part of natural law, which is called multiculturalism. Cultural pluralism is not separated from democracy. Democracy is a system of state which is regulated constitutionally and legitimizes all interests and rights of the individuals.